2018
DOI: 10.17953/aicrj.42.4.elkotni
|View full text |Cite
|
Sign up to set email alerts
|

Between Cut and Consent: Indigenous Women's Experiences of Obstetric Violence in Mexico

Abstract: In an effort to improve health outcomes, the proportion of hospital-attended births has been on the rise in Mexico since the 1990s, resulting in an increased medicalization of reproductive health. Ethnographic research in southern Mexico highlights women and Indigenous midwives' ambivalence about “being cut.” While “being cut” can refer to procedures such as episiotomies or cesarean sections, it also stands for Indigenous and poor women's multiple experiences of frustration, mistreatment, and violence during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Feminist analyses locate obstetric mistreatment within extant power matrices, with disrespect and abuse occurring atop pre‐existing power dynamics 17–19 . Thus, we situate our findings within the broader literature on intersectionality as a factor that produces amplified exposure to oppression and vulnerability to harm 20–22 …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Feminist analyses locate obstetric mistreatment within extant power matrices, with disrespect and abuse occurring atop pre‐existing power dynamics 17–19 . Thus, we situate our findings within the broader literature on intersectionality as a factor that produces amplified exposure to oppression and vulnerability to harm 20–22 …”
Section: Discussionmentioning
confidence: 72%
“…[17][18][19] Thus, we situate our findings within the broader literature on intersectionality as a factor that produces amplified exposure to oppression and vulnerability to harm. [20][21][22] Globally, studies on mistreatment have reported wide-ranging differences in estimated prevalence, using an assortment of measurement instruments and techniques. When compared with the single other study using this same instrument and approach, 16 we found a comparatively lower prevalence of mistreatment than those found in Nigeria, Ghana, and Myanmar.…”
Section: Discussionmentioning
confidence: 99%
“…This strips women of their identities, cultural and spiritual values, and traditions, and alienates them from important social networks and traditional medical assistance (Sadler 2004; Belli 2013; Gonzalez-Flores 2015; Martins and Barros 2016). Indeed, “[f]or Indigenous women, for whom the conquest of the land was also the conquest over their bodies, these intimate intrusions [mandatory vaginal examinations in clinical settings] are reminiscent of colonial practices,” and hospitals become a place that reproduces domestic, structural, and political violence inherent in colonial practices (Kotni 2018). Biomedicine's broader social legitimization invalidated and replaced women and traditional birth attendants as agents of authoritative knowledge in childbirth and it colonized social perceptions of what counts as “normal” childbirth (Sadler 2004; Belli 2013; Castro and Savage 2019; Sadler 2020), thus rendering violations in childbirth normal and largely invisible (Sadler 2004).…”
Section: The Conceptual Landscape and Emerging Contestationsmentioning
confidence: 99%
“…39 In 2013 the National Commission to Prevent and Eradicate Violence Against Women reported that "at least 27 percent of Indigenous women who have been in contact with public health services have been sterilized without their consent." 40 Many poor women in Chiapas were most certainly harmed in their attempts to secure pregnancy termination given that illegal abortion was the third-leading cause of maternal mortality in the country, and rates of maternal mortality among Indigenous women were the highest in the country. 41 The National Coordinator of Indigenous Peoples supported the abortion law, stating in a letter to President Carlos Salinas de Gortari that the Chiapas law "does no more than recognize the clamor of hundreds of thousands of women, today and in another time, who have died from having been forced into unwanted motherhood."…”
Section: Abortion Debate In Chiapasmentioning
confidence: 99%